2020
DOI: 10.3390/agronomy10071028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proteomic Profile of Contrasting Phosphorus Responsive Rice Cultivars Grown under Phosphorus Deficiency

Abstract: Phosphorus (P) deficiency is one of the major limiting factors for crop productivity. The yield of rice (Oryza sativa L.) is severely limited by phosphorus deficiency. An attempt has been made in this study to identify P deficiency responsive differentially expressed proteins of rice through analysis of leaf proteome of contrasting P-responsive rice cultivars under P deficiency conditions because genetic variability has been found in the rice cultivars for adaptive response to P deficiency and a controlled reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For proteome profiling, two-dimensional electrophoresis (2-DE) was performed according to the method of O’Farrell [ 107 ]. An immobilized dry strip gel (11 cm, linear-gradient, pH 4–7) was rehydrated at 20 °C for 12 h in 180 μL of a sample containing 350 μg proteins [ 108 ]. The first dimension, i.e., isoelectric focusing, was accomplished by an isoelectric focusing (IEF) apparatus (PROTEAN ® i12™ IEF Cell, Singapore).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For proteome profiling, two-dimensional electrophoresis (2-DE) was performed according to the method of O’Farrell [ 107 ]. An immobilized dry strip gel (11 cm, linear-gradient, pH 4–7) was rehydrated at 20 °C for 12 h in 180 μL of a sample containing 350 μg proteins [ 108 ]. The first dimension, i.e., isoelectric focusing, was accomplished by an isoelectric focusing (IEF) apparatus (PROTEAN ® i12™ IEF Cell, Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…For mass-spectrometry analysis, the differentially expressed protein spots were excised and destained with 50 mM ammonium bicarbonate and dehydrated with 100% acetonitrile (ACN), and then digested with 15 µL of working trypsin (10 ng µL −1 ) (Molecular grade, Promega, Madison, WI, USA) overnight at 37 °C [ 108 ]. The final volume was subjected to a mass spectrometer (MALDI MS—ABI Sciex 5800 TOF/TOF System, Massachusetts, USA) controlled by the Flexcontrol 2.4 package using set parameters with the peptide charge of 1+ and peptide tolerance of 150 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…The malate dehydrogenase down-regulation could contribute to the changes seen in M. malabathricum photosynthetic activity as can be seen in citrus and transgenic tomato by way of mMDH reduced expression (Huang et al 2020;Nunes-Nesi et al 2005). Studies on the response of malate dehydrogenase in As stress (Alcántara-Martínez et al 2018;Chauhan et al 2020), phosphorus deficiency (Tantray et al 2020) and under salt stress (Long et al 2019) were reported. Malate dehydrogenase was up-regulated on day three of drought stress and continued elevated until day seven by contrast with control (Gupta et al 2020a, b).…”
Section: Varied Expression Pattern Of Nucleotide Metabolismmentioning
confidence: 99%
“…The performance of crops under abiotic and biotic stresses was analyzed regarding pests, diseases, and abiotic factors. The cereals studied were triticale (×Triticosecale Wittmack) [24], wheat [25], rice [26,27], and barley (Hordeum vulgare L.) [28]. Resistance to diseases as rust and powdery mildew, together with blast resistance, phosphorous deficiency, and salt stress were evaluated in this group of crops.…”
mentioning
confidence: 99%
“…This study aimed to identify P-deficiency-responsive differentially expressed proteins in rice through analysis of leaf proteome of contrasting P-responsive rice cultivars under P-deficiency conditions because genetic variability has been found in rice cultivars for adaptive response to P deficiency, and a controlled regulatory system is involved in the P deficiency adaptation response. This study could help to unravel the complex regulatory process that is involved in adaptation to P deficiency in rice [27]. The interaction between salinity and nitrogen metabolism has been investigated in two barley landraces, one tolerant ("100/1B") and one susceptible to salinity ("Barley medenine") from the Middle East and North Africa region.…”
mentioning
confidence: 99%